UPAYA KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR RODA DUA (STUDI KASUS : POLRES TANAH KARO) - Agra Putra Riady Purba; Maria Ferba Editya S; Rayani Saragih (Journal Recht (JR), 2022)
This study discusses the police's efforts in tackling the crime of theft of two-wheeled motorized vehicles (case study: Polres Tanah Karo).. The type of legal research carried out in a normative juridical manner is a normative juridical where the law is conceptualized as what is written in laws and regulations (law in books) or the law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. This normative legal research is based on primary and secondary legal materials, namely research that refers to the norms contained in the legislation. The results of this study indicate that the cause of motorcycle theft in Tanah Karo is caused by two factors, namely internal factors where internal factors include intelligence, age and economy. And external factors include association and education. efforts to improve the obstacles faced by the Tanah Karo Police in dealing with criminal acts of motor vehicle theft, it is hoped that the number of motor vehicle theft crimes that occur at the Tanah Karo Police Station can decrease. Because the obstacles faced by the Tanah Karo Police can be corrected with the efforts that have been described in the improvement efforts carried out by the Karo Tanah Karo Police. in accordance with the objectives of crime or crime prevention. The aim is to create an atmosphere of society free from physical and psychological disorders, an atmosphere free of worries, doubts, and fears, as well as a sense of certainty and obedience to the law, a community atmosphere that feels protection from all kinds of dangers, an atmosphere of peace and tranquility